Efektivitas Pemberian Buah Pisang Raja untuk Menurunkan Kelelahan Kerja pada Operator Sewing UMKM Garmen X Karanganyar - Gavra Prachristma Sujudi, Virginia Bernardine; Wardani, Tyas Lilia; Sari, Rizqy Kartika (UI Scholars Hub, 2025)
Work fatigue is a common problem that can reduce productivity and increase the risk of workplace accidents. At UMKM Garmen X Karanganyar, the lack of supplementary food intake causes energy deficits and fatigue among workers. This condition underlies the research to analyze the effectiveness of giving banana raja (Musa paradisiaca L.) as an additional snack in reducing work fatigue among sewing operators at UMKM Garmen X Karanganyar. The research was conducted using a true experimental method with a pre-test and post-test design with a control group. 42 sewing operators were selected from 47 workers using simple random sampling, divided into two groups of 21 people each. The experimental group received an intervention of 100 grams of banana raja for 4 consecutive days. Work fatigue was measured using the Swedish Occupational Fatigue Index (SOFI) questionnaire before and after the intervention, then analyzed using paired sample t-test and independent t-test statistical tests. The results showed that there was no significant difference in work fatigue in the control group p = 0,060 (p > 0,05) and there was a significant difference in work fatigue in the experimental group p = 0,001 (p < 0,05). Work fatigue between the control and experimental groups showed a significant difference p = 0,001 (p < 0,05) with an effect size (d) of 1,74. The provision of banana raja is significantly effective in reducing work fatigue among sewing operators at UMKM Garmen X Karanganyar. Keywords: Occupational Nutrition, Sewing Operator, Raja Banana, SOFI, Work Fatigue